2014
DOI: 10.1089/lap.2014.0006
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal Laparoscopic Nephrectomy for Acute Blunt Grade 4 Renal Injuries

Abstract: Despite the technical challenges, LN for patients with acute blunt Grade 4 renal injuries using a retroperitoneal approach is safe and feasible in carefully selected patients if conservative measures and angiographic embolization fail. However, it is important to note that one should keep a low threshold for open conversion or the hand-assisted approach whenever necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…Design of included studies: 3 articles were case reports and 1 was a case series. [11][12][13][14] Region of study origin: Included studies were conducted in Australia, Italy, India and China. [11][12][13][14]…”
Section: Resultsmentioning
confidence: 99%
“…Design of included studies: 3 articles were case reports and 1 was a case series. [11][12][13][14] Region of study origin: Included studies were conducted in Australia, Italy, India and China. [11][12][13][14]…”
Section: Resultsmentioning
confidence: 99%
“…reported for the first time LN (retroperitoneoscopic) following acute renal trauma within 24 h of trauma after failed embolisation. [2]…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al themselves reported haematoma rupture before arterial control in one out of two cases. [2] Further, a large haematoma will not allow retroperitoneoscopic approach. Assessment of diaphragmatic injury will be easier in transperitoneal approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Доступ в поясничной области подходит только для плановой урологической ситуации. Появилось пер-вое сообщение о лапароскопической нефрэктомии при травме почки у 3 пострадавших [106].…”
unclassified